Formation and development of the pore structure in Chang 7 member oil-shale from Ordos Basin during organic matter evolution induced by hydrous pyrolysis. (15th October 2015) - Sun, Lina; Tuo, Jincai; Zhang, Mingfeng; Wu, Chenjun; Wang, Zixiang; Zheng, Youwei
Highlights: The pore evolution process of oil-shale was simulated by hydrous pyrolysis. The nitrogen quantity adsorbed increased with increasing pyrolysis temperature. The development of the pore structure was associated with organic matter evolution. The pyrolysis products in different thermal stages may be the basic factor to affect porosity. The pore evolution was roughly divided into the stages of reforming, formation and development. Abstract: To obtain information about the pore characterization during the evolution of sedimentary organic matter, the pore structures of residual samples from oil-shale hydrous pyrolysis experiments were analyzed via low-pressure nitrogen adsorption measurements. These seven experiments were conducted at different temperatures, while other experiment factors, such as original samples, the heating time and rate, the lithostatic pressure and the hydrodynamic pressure, were kept same. Nitrogen adsorption measurements were performed on unheated samples and other solid residues after pyrolysis at different simulation temperatures to analyze and characterize the nature of the pore structure. The results showed that Type IV nitrogen adsorption isotherms with Type H3 hysteresis loops are present in these samples, so mesopores may be predominant. With increasing pyrolysis temperature, the quantity of nitrogen adsorbed generally presents an increasing trend at a relative P / P 0 value of approximately 0.996 MPa. The total pore volume and specific surface area were positively correlated with the pyrolysis temperature, and their correlation coefficients ( R 2 ) were 0.91 and 0.83, respectively. The pore volume and surface area of the micropores, mesopores and macropores all increased, as did the quantities of the corresponding pores. By combining the different scales of pore development with the pyrolysis products, a model for the stages of porosity evolution was acquired. With the increasing simulation temperature, the changing of porosity calculated roughly by the decreased amount of TOC present a same tendency with the measured values by N2 adsorption method. But the relative deviation between them was higher in lower maturity, the opposite occurred in higher maturity. Therefore, the effect of TOC on the evolution of pore structure may be related to the maturity. And the pore connectivity which resulted from the generation and migration of pyrolysis products, can be seen as the important factor on the increased porosity. In further level, shale oil–gas were better preserved in lower maturity, but likely to migrate in higher thermal evolution.